HIV-1 Vpu represents a minor target for cytotoxic T lymphocytes in HIV-1-infection. - Addo, M; Altfeld, M; Rathod, A; Yu, M; Yu, X; Goulder, P; Rosenberg, E; Walker, B (2002)
We have previously shown that Vpu is rarely targeted by HIV-1-specific cytotoxic T lymphocytes (CTL). The present report extends these findings and describes the characterization of the first CTL epitope within HIV-1 Vpu, identified in an individual with long-term non-progressive HIV-1 infection. The epitope was shown to be highly conserved among HIV clade B sequences and is restricted by HLA-A*3303, an HLA allele commonly seen in Asian and west-African populations.